(untitled) (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2024)
In this article, the relevance of the development of communicative competence of students on the basis of innovative approaches, the importance of communicativity in personality maturation, theoretical foundations of communicative competence, requirements for a modern teacher, ensuring the achievement of the development of communicative abilities through the use of effective methods in the educational process, developing and introducing effective methodologies based on, information and recommendations have been made regarding the search for new strategies to increase communicativity.